A review on smart bioresponsive drug delivery systems - Kainat Haleem; Muhammad Arslan Khan (AMMANIF, 2019)
During the past several decades, many sensing mechanisms have emerged, which provide new control strategies for designing closed-loop drug delivery systems. For such systems, numerous bioresponsive materials are utilized to construct functional modules for the desired devices. The typical closed-loop drug delivery systems recently reported in this review. The stimuli-responsive polymers serve to provide a snapshot of the utility and complexity of polymers that can sense, process, and respond to stimuli in modulating the release of a drug. Stimuli-responsive drug delivery vehicles come in the form of polymersomes, liposomes, micelles and dendrimers. Therapeutics is designed to be controlled released from drug carriers through the structural transformations such as shrinking, swelling, and dissociation or unique responsive cleavage route.